The Influence of Self Efficacy on Work Family Conflict in Mothers Who Work as Teachers During the Covid-19 Pandemic - Mutiara Bilqis Afifah, Sabda; Pepayosa, Emya; Tria Mustika, Rizky (International Journal of Social Science, Education, Communication and Economics, 2024)
This research aims to find out whether there is a significant influence of self-efficacy on work family conflict in mothers who work as teachers during the Covid-19 pandemic. This research uses a quantitative approach using a questionnaire. The measuring instruments used in this research are the Work Family Conflict Scale to measure work family conflict and Sherer et al General Self Efficacy Scale (SGSES) to measure self efficacy. The sample in this study was 152 mothers who worked as teachers and had elementary school age children. This research data analysis method uses simple linear regression analysis to see the influence of the independent variable, namely self-efficacy, on the dependent variable, namely work family conflict. The results of this research show that self-efficacy has a significant effect on work family conflict in mothers who work as teachers during the Covid-19 pandemic with a value of sig=0.000 and R2=0.184. The influence of self-efficacy on work family conflict is 18.4%.